Improving Crop Yields in Sub-Saharan Africa : What Does the East African Data Say - Thomas, Alun. (Washington, D.C. : International Monetary Fund, 2020)
Recent micro level data from East Africa is used to benchmark aggregate data and assess the role of agricultural inputs in explaining variation in crop yields on smallholding plots. Fertilizer, improved seeds, protection against erosion and pesticides improve crop yields in Rwanda and Ethiopia, but not Uganda, possibly associated with lack of use there. With all positive yield determinants in place, wheat and maize yields could increase fourfold. The data hints at the negative effect of climate change on yields and the benefits of accompanying measures to mitigate its adverse impact (access to finance and protection against erosion). The adverse effect of crop damage on yields varies between 12/13 percent (Rwanda, Uganda) to 36 percent (Ethiopia). Protection against erosion and investment financing mitigate these effects considerably.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet